Opportunities, barriers and incentives for multistakeholder collaboration and investment in rangeland restoration in Colombia. - Valencia Salazar, Sara (International Livestock Research Institute, 2025)
This report explores the challenges, opportunities and incentives for stakeholder investment in grassland restoration in Colombia. It emphasizes the importance of sustainable livestock farming in the context of Colombia’s biodiversity-rich ecosystems, particularly the grasslands of the Orinoquia Region. These ecosystems are facing degradation due to overgrazing, unsustainable land-use practices and deforestation. Restoration of these ecosystems is vital for environmental conservation and improving livestock productivity and mitigating climate change through carbon sequestration.